Answer:
x = 36
Step-by-step explanation:
(3/4)*x-((2/3)*x)-4 = (1/6)*x-7 // - (1/6)*x-7
(3/4)*x-((2/3)*x)-((1/6)*x)-4+7 = 0
(3/4)*x+(-2/3)*x+(-1/6)*x-4+7 = 0
3-1/12*x = 0 // - 3
-1/12*x = -3 // : -1/12
x = -3/(-1/12)
x = 36
Answer:
B
Step-by-step explanation:
5x - 1 = x =4
Answer:
Good For Her
Step-by-step explanation:
She is now in debt of 43,000 and she will now be poor
Answer:
No, because the sample was randomly selected.
Step-by-step explanation:
In this example, the main element that we need to focus on is the way in which the sample was determined. We learn that the sample was taken in California with 1000 people. However, this sample was random, and the survey was conducted in both English and Spanish. The fact that this was a random sample means that it is representative of the population. The size of the population does not affect the accuracy of a random sample.
Answer:
864
Step-by-step explanation:
Volume of cup = ⅓pi×r²×h
Diameter = 2, radius = 1
= ⅓×3.142 × 1² × 4 = 4.1893333333 in³
To empty the sink, 864 scoops will be required
(3617/4.1893333 = 863.383)